Facile Synthesis of Conductive Flexible Composite Sn@Ag Microspheres and their Application in Anisotropic Conductive Films. (5th December 2021) - Zhang, Wen Hua; Fan, Pei Yuan; Yu, Xianglei; Cheng, Jun Hua; Cheng, Ding Xiang; Liu, Cheng Bing; Gan, Guo You; Li, Jun Peng
Abstract: Composite microspheres with noble metal nanoshells are advantageous in flexible circuit connections, flip chips, and chemical sensors. It is difficult for Polystyrene microspheres to cover a complete Ag layer, and hard metal microspheres have no deformability. These two reasons have contributed to this research. This report demonstrates a facile synthesis route that chemically deposits an Ag layer on the surface of 30 µm Sn microspheres to form a composite Sn@Ag double‐layer structure, which is suitable for anisotropic conductive films (ACFs) with linewidths greater than 100 µm. Scanning electron microscope analysis reveals that the surface Ag coating thickness can be controlled within the range of 737 nm–5.62 µm by varying the amount of Ag source applied, and trace free Ag particles are produced during the preparation process. An anisotropic conductive adhesive film is successfully fabricated and hot‐pressed after the film‐on‐film flexible circuit board. The microspheres form an ACF single‐layer structure after hot pressing. Hot pressing in the range of 10–20 MPa can ensure deformation and avoid Ag shell cracking, and the deformation is determined when Sn@Ag is in contact with the circuit surfaces at both ends. This approach provides a potential method of preparing low‐cost and high‐performance ACFs. Abstract : The Sn@Ag composite microspheres synthesized by the reduction method are successfully mixed with resin, and a new type of anisotropic conductive adhesive film for microelectronics packaging is obtained. In addition, the deformation properties of this Sn@Ag and the conductivity of the anisotropic conductive films when connected to thin‐film circuits are studied.